Postepidemic analysis of Rift Valley fever virus transmission in northeastern kenya: a village cohort study. - A Desirée LaBeaud; Samuel Muiruri; Laura J Sutherland; Saidi Dahir; Ginny Gildengorin; John Morrill; Eric M Muchiri; Clarence J Peters; Charles H King (Public Library of Science (PLoS), 2011)
In endemic areas, Rift Valley fever virus (RVFV) is a significant threat to both human and animal health. Goals of this study were to measure human anti-RVFV seroprevalence in a high-risk area following the 2006-2007 Kenyan Rift Valley Fever (RVF) epidemic, to identify risk factors for interval seroconversion, and to monitor individuals previously exposed to RVFV in order to document the persistence of their anti-RVFV antibodies.We conducted a village cohort study in Ijara District, Northeastern Province, Kenya. One hundred two individuals tested for RVFV exposure before the 2006-2007 RVF outbreak were restudied to determine interval anti-RVFV seroconversion and persistence of humoral immunity since 2006. Ninety-two additional subjects were enrolled from randomly selected households to help identify risk factors for current seropositivity. Overall, 44/194 or 23% (CI(95%):17%-29%) of local residents were RVFV seropositive. 1/85 at-risk individuals restudied in the follow-up cohort had seroconverted since early 2006. 27/92 (29%, CI(95%): 20%-39%) of newly tested individuals were seropositive. All 13 individuals with positive titers (by plaque reduction neutralization testing (PRNT₈₀) in 2006 remained positive in 2009. After adjustment in multivariable logistic models, age, village, and drinking raw milk were significantly associated with RVFV seropositivity. Visual impairment (defined as ≤ 20/80) was much more likely in the RVFV-seropositive group (P<0.0001).Our results highlight significant variability in RVFV exposure in two neighboring villages having very similar climate, terrain, and insect density. Among those with previous exposure, RVFV titers remained at > 1∶40 for more than 3 years. In concordance with previous studies, residents of the more rural village were more likely to be seropositive and RVFV seropositivity was associated with poor visual acuity. Raw milk consumption was strongly associated with RVFV exposure, which may represent an important new focus for public health education during future RVF outbreaks.